What can we learn from the ecophysiology of plants inhabiting extreme environments? From ‘sherplants’ to ‘shercrops’ - Flexas, Jaume (2025)
In the 19th century it was proposed that ecophysiology was best studied in regions with extreme climatic conditions. In the present perspective, we argue that perhaps this is more timely than ever. The main reason is the need to improve crops to be simultaneously more productive—due to the increased population—and more stress tolerant—due to climate change. Climate change induces plants to face not just harsh but also ‘unexpected’ (unpredictable) climatic conditions. In this sense, we hypothesize that ‘sherplants’, namely plants living in the extremes of plant life (e.g. hot deserts, Arctic and Antarctica, or high elevations) can provide cues on how to break the trade-off between productivity and stress tolerance, as they need to be produced quickly due to the very short growing period while being stress tolerant due to the harsh and unpredictable climate endured during most of the year. We present glimpses of results from three consecutive projects developed over the last 10 years, in which hundreds of species from different regions of the world have been studied. In particular, we propose a pathway for developing ‘shercrops’ learning from ‘sherplants’, debate whether some of the already studied species may have really broken the aforementioned trade-off, and present a number of interesting unforeseen discoveries made when studying plants from extreme climates.